Profile of Secondary Metabolites and Study of Antibacterial Activity of Ethanol Extracts of Mulberry Fruit (Morus alba) in Inhibiting Escherichia coli and Staphylococcus aureus - Seftya Putri Mahyantika; Abdoes Sjakoer, Nour; Ramadhan, Majida (JSMARTech: Journal of Smart Bioprospecting and Technology, 2025)
Mulberry fruit is known as a medicinal plant with various health benefits, including as an antibacterial agent. This study aims to identify the content of secondary metabolites and evaluate their antibacterial activity. The methods used in this study were experiments with qualitative and quantitative approaches. Extraction was performed using ethanol as a solvent with the maceration technique, while phytochemical analysis was conducted using specific reagent tests to detect the presence of bioactive compounds. Antibacterial activity testing was carried out using the disc diffusion method with varying concentrations of the extract at 25%, 50%, 75%, and 100%. Phytochemical analysis results showed that mulberry fruit extract contains alkaloids, flavonoids, phenols, saponins, tannins, and triterpenoids. Antibacterial activity testing against Escherichia coli produced inhibition zones of 19.25 mm, 20.33 mm, 26 mm, and 27.17 mm, respectively, while for Staphylococcus aureus, the inhibition zones were 17.58 mm, 20.08 mm, 25.75 mm, and 30.92 mm, respectively. In general, the inhibition zones formed showed an increase with increasing extract concentration. However, statistically, there was no significant difference in inhibiting both bacteria. Based on these results, mulberry fruit extract has balanced antibacterial potential against both Gram-positive and Gram-negative bacteria, making it a promising candidate for development as a broad-spectrum natural antibacterial agent. Keywords: antibacterial, Escherichia coli, mulberry, phytochemical screening, Staphylococcus aureus